The Effects of Total Physical Response and Storytelling on English Major Undergraduate Student’s Listening and Speaking Skills - Sonthirak, Thanaphat; Lertphatiwong, Suphawee; Boonjanda, Phawinee; Lakhamja, Rungsan; Rawengwan, Wimolporn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The objectives of this research were to 1. study the effects of the total physical response and storytelling methods on English major undergraduate students’ listening and speaking skills and 2) examine the students’ satisfaction on the total physical response and storytelling methods. The sample consisted of 200 first to fourth year students studying in English major at the Faculty of Humanities and Social Sciences at Nakhon Sawan Rajabhat University. This quantitative study was a quasi-experimental research employing the use of 1. pre-test and post-test, 2. questionnaires, and 3. instructional plans. The data were statistically analyzed with the use of percentage, mean, and standard derivation. The results revealed that the students’ post-test scores (15.94) of listening and speaking were significantly higher than those of the pre-test scores (11.44) at the significant level of 0.05 after the implementation of total physical response and storytelling, which showed that the students had remarkable improvement in listening and speaking. In addition, the students’ satisfaction towards the two methods was at the highest level as they considered both total physical response and storytelling enjoyable and advantageous to their listening and speaking enhancement.